Towards an Intercivilizational Turn: Naoki Sakai's cofigurative regimes of translation and the problem of Eurocentrism. Issue 1 (2nd January 2016) - Robinson, Douglas
ABSTRACT: The rather inflamed debate over Eurocentrism in Translation Studies over the past few years seems to be pointing to a new Turn in TS, following on the Cultural Turn of the 1990s and the Sociological Turn of the 2000s: an Intercivilizational Turn, focused no longer on "centers" of "civilization" but the interstices and relationships between civilizations. Orientalism has long been one such intercivilizational relationship; Occidentalism has more recently been emerging as a rival to that. The article seeks to show that much of what we take to be most innovative in both the "Eurocentric"/"Orientalist" and the "Occidentalist" approaches to TS has emerged out of the influence of Chinese thought on Western thinkers.